Hubungan antara Pengetahuan Mikrobiologi dengan Sikap Hygiene Mahasiswa Akper Kesdam I/BB Padang - Vevi Kurniawati (Akper Kesdam I/Bukit Barisan Padang, 2020)
Diseases in humans can be causesd by pathogenic microorganisms that arise due to unsanitary attitudes. Hygiene attitude is an attitude that cannot be separated from human life. Hygiene attitudes can be achieved by having by having the correct microbiological knowledge that can improve the level of hygiene. The purpose of this study was to determine the relationship between microbiological knowledge and the hygiene attitudes of the students of the Akper Kesdam I/BB Padang. The research method used is a survey method with a correlational study. The population of this study were 82 students in semester 3 and 6 who had taken microbiology courses. Sampling using random sampling technique as 40 people. The study was conducted December 2020. The results of this study found that the two variables had a relationship with a contribution of 11,4% to the significant level α = 0.05 (5%) where r count (0,338) > r tabel (0,312).